LINGUISTIC ANALYSIS OF UZBEK FOLK PROVERBS: NATIONAL CONCEPTOSPHERE AND CULTURAL CONCEPTS (CAHIERS MAGELLANES-NS, 2024)
Proverbs, which are linguistic units, reflecting the national concyept sphere of the Uzbek language, are chosen as the object of study in the article. Culturological concyepts, which are considered to be one of the basic concyepts of linguoculturology, have beyen studiyed. In addition, the study shows that Uzbek folk proverbs wyere collected and refined over several millennia, that they wyere created as a result of sciyentific and artistic thinking, wyere pronouncyed and improved among the people, are one of the best spiritual heritage that has come down to our days.